The Relationship between Large Herbivore Abundance and Algal Cover on Coral Reefs on West Coast Barbados - Caron, Vanessa; Greiner, Ariel; Ransier, Krista; Cameron-Steinke, Bryna (McGill Science Undergraduate Research Journal, 2016)
Background: Over the past few decades, climate change and the intensification of coastal development significantly contributed to the degradation of coral reefs across the Caribbean Sea. Widespread increase in algal cover on coral reefs since the 1970s has made it difficult for the corals to recover. Thus, algae regulating factors, such as herbivorous grazers and groundwater nutrient concentrations, have important implications for the conservation of coral reefs. In this study we conducted a small-scale assessment of the relationship between the abundance of two families of herbivorous fishes, Scaridae and Acanthuridae, and algal cover on the coral reefs of West Coast Barbados was conducted, and we hypothesized that a direct negative correlation exists between them. Methods: Herbivorous fish abundance and percent algal cover were quantified for three different coral reefs, and the data was analyzed using linear regressions and analyses of variance. Results: We found that although there were no significant relationship between herbivorous fish abundance and algal cover, there was a significant difference between them across the three reefs studied. These results suggest the presence of other factors influencing algal cover. One such factor could potentially be ground- water input levels, which was found to differ at each of the three sites studied. Limitations: The limited timeframe of this study did not allow for extensive sampling. Conclusion: In order to effectively protect the coral reefs in Western Barbados, Further studies are needed to increase the understanding of the relationship between herbivory and algal cover in Western Barbados as well as to further investigate the role of groundwater seepage on algal growth.